Exploring Prejudicial Ethnic Attitudes Among Young Malaysian Adults: A Case Study Of Malay And Chinese Students In A Public University - Ng, Sen Fa (2014)
This study attempts to model and explain ethnic attitudes among undergraduates in a public university in Malaysia (n=1551) using Confirmatory Factor Analysis (CFA) and Structural Equation Modelling (SEM). Malaysia’s socio-historical background of ethnic relations and theories that explain individual’s ethnic attitudes are introduced. The research provides theoretical significance by suggesting new executable variables, introducing multivariate framework situated in the Malaysia context. Various variables and their operationalization such as upbringing backgrounds, psycho-social indicators and their interplay in relation to ethnic attitudes were proposed. The proposed models suggest that Malaysian young adults’ prejudiced attitudes are mainly driven by these factors: 1) in-group cohesion to defend one’s self-interest, 2) frustration from perceived deprivation and, 3) value-culture conflicts. Multi-group analysis supported unconstrained model paths coefficients for Malays and Chinese students, indicates that each group’s ethnic attitudes are qualitatively different. Group size is related to willingness to befriend others of different ethnicity, Chinese and Malay respondents reported significant resistance to multi-ethnic friendships. Conversely, minority groups also reported significant egalitarian values. The insights engendered provide important complementary understanding to other structural factors underlying ethnic relations in Malaysia. (181 words).